Applying Youtube Kids to Foster Children Vocabulary Mastery at Ihya Al-Ulum Kindergarten - Muhammad Chairil Imran; Nasaruddin Nasaruddin (South Sulawesi Education Development (SSED), 2022)
The research was generally discussing the use of Youtube Kids to foster the vocabulary mastery of children at Ihya Al-Ulum Kindergarten. The researchers selected the sample from the population by using total sampling technique. The number of the sample was 25 children. This research was a pre-experimental design with one group pretest and posttest. The group was tested after treatment, the test included pretest and posttest that consisted of 25 items. The result of data analysis showed that there was a significant difference between the mean scores of pretest and posttest. The mean score of posttest was greater than the mean score of pretest. The means score of pretest was 51.7 and the mean score of posttest was 66.1. Then, the T-test value was 6.65 and T-table value was 1.699 with df = 24 and α = 0.05. It can be concluded that the use of Youtube Kids can foster children vocabulary mastery. It means that there is a significant difference (H1) of the children vocabulary mastery before and after treatment by using Youtube Kids.